2023
DOI: 10.1186/s13054-023-04376-y
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, double-blind trial comparing the effect of two blood pressure targets on global brain metabolism after out-of-hospital cardiac arrest

Abstract: Purpose This study aimed to assess the effect of different blood pressure levels on global cerebral metabolism in comatose patients resuscitated from out-of-hospital cardiac arrest (OHCA). Methods In a double-blinded trial, we randomly assigned 60 comatose patients following OHCA to low (63 mmHg) or high (77 mmHg) mean arterial blood pressure (MAP). The trial was a sub-study in the Blood Pressure and Oxygenation Targets after Out-of-Hospital Cardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…There was no difference in the primary outcome (a composite of death or poor functional outcome at 90 d) which occurred in 34% of those in the 77 mm Hg group compared with 32% in the 63 mm Hg group (hazard ratio, 1.08; 95% CI, 0.84–1.37; P =0.56). In a sub-analysis of this study, lactate-to-pyruvate ratios in jugular venous blood, markers of global brain metabolism, were also no different between the groups 24. The mean difference in achieved MAP between the 2 groups was 10.7 mm Hg, which may have been too small to affect clinical outcomes.…”
Section: Current Evidencementioning
confidence: 50%
See 1 more Smart Citation
“…There was no difference in the primary outcome (a composite of death or poor functional outcome at 90 d) which occurred in 34% of those in the 77 mm Hg group compared with 32% in the 63 mm Hg group (hazard ratio, 1.08; 95% CI, 0.84–1.37; P =0.56). In a sub-analysis of this study, lactate-to-pyruvate ratios in jugular venous blood, markers of global brain metabolism, were also no different between the groups 24. The mean difference in achieved MAP between the 2 groups was 10.7 mm Hg, which may have been too small to affect clinical outcomes.…”
Section: Current Evidencementioning
confidence: 50%
“…In a sub-analysis of this study, lactate-to-pyruvate ratios in jugular venous blood, markers of global brain metabolism, were also no different between the groups. 24 The mean difference in achieved MAP between the 2 groups was 10.7 mm Hg, which may have been too small to affect clinical outcomes.…”
Section: Blood Pressure and Cerebral Perfusionmentioning
confidence: 90%
“…In a study investigating the impact of mean arterial blood pressure regulation on the neurological prognosis of OHCA patients through JB based brain metabolism monitoring, lactate/pyruvate ratio exceeding 16 was defined as ischemia when pyruvate is below 70 μM, and exceeding 70 μM was defined as mitochondrial dysfunction. The study reported that mean arterial blood pressure regulation does not improve neurological prognosis in patients with OHCA 28 . In this study, no significant agreement was observed between CSF and JB lactate levels in patients with a good neurological prognosis.…”
Section: Discussionmentioning
confidence: 89%
“…In critically ill patients, mean arterial pressure (MAP) represents the entry pressure for the perfusion of most organs and should be maintained >65–70 mmHg [ 116 , 117 , 118 ]. Although higher MAP levels may be required in patients with brain injury or persistent hypoperfusion (e.g., progressing acute kidney injury or altered mental status) [ 119 , 120 ], adequate circulatory volume, absence of left ventricular outflow tract obstruction, and microcirculatory flow and responsiveness (if possible) should be ideally assessed before using a vasopressor challenge, especially in patients treated with TTM [ 77 , 121 , 122 , 123 ].…”
Section: Circulatory Managementmentioning
confidence: 99%